Leaf Defoliation Tolerance of Root-Cutting Chili Varieties (Capsicum annum L.) Planted in Lowland Areas Related to Improve Yield and Physiological Activity - Kusumaningrum, Sarlin; Sulistyaningsih, Endang; Harimurti, Rudi; Dewi, Kumala (Trends in Sciences, 2025)
Lowland chili (Capsicum annum L.) cultivation in Indonesia has lower productivity than highlands. Root-shoot growth increment can enhance chili yield. Leaf defoliation with root cutting is modification technique to optimize root-shoot growth. This research aims to determine improving physiological activity and yield of root-cutting chili varieties tolerant to leaf defoliation in lowland areas. The factorial treatments were arranged in randomized complete block design with 3 replications. The first factor was lowland chili varieties (Kencana, Lembang-1, Tanjung-2, and Ungara). The second factor was leaf defoliation on root-cutting chili, consisting of 0, 20, 40, 60 %, and control (0 % leaf defoliation without root-cutting). Analysis of variance was used to determine effect of leaf defoliation on physiological activity and chili yield. The grouping chili varieties were analyzed through principal component and cluster analysis based on yield, stress selection indices, and physiological activity. The result identified Lembang-1 and Ungara as tolerant varieties to leaf defoliation, while Kencana and Tanjung-2 were intolerant. Ungara and Lembang-1 could increase fresh weight of fruit by 39.26 and 29.30 %, respectively under 40 and 60 % leaf defoliation compared to control. The increased chili yield and root-shoot growth in tolerant varieties were caused by improving physiological activity. Root growth was driven by increased invertase activity, reducing sugar, indole acetic acid, and kinetin hormones, while shoot growth was influenced by increased sucrose, invertase activity, reducing sugar, gibberellin, and kinetin hormones. Leaf defoliation until 60 % on intolerant varieties (Tanjung-2 and Kencana) decreased chili yield by 9.53 and 19.64 %, respectively. It was concluded that 40 and 60 % leaf defoliation treatment were toleranted by root-cutting chili varieties of Ungara and Lembang-1, which increased chili yield in lowland areas. HIGHLIGHTS This research provides information on chili production improvement in lowland areas using root-shoot growth modification through root cutting and leaf defoliation. Response root-cutting chili yield based on stress selection indices, phytohormones, sucrose content, invertase activity, and reducing sugar under leaf defoliation was classified into tolerant (Lembang-1 and Ungara) and intolerant (Tanjung-2 and Kencana). The tolerant varieties (Lembang-1 and Ungara) could increase fresh weight of fruit by 29.30, 39.26 %, respectively under 60 and 40 % leaf defoliation compared to control (0 % leaf defoliation without root-cutting). The increased chili yield and root-shoot growth were due to physiological activity. Root growth was driven by increased invertase activity, reducing sugar, indole acetic acid, and kinetin hormones, while shoot growth was influenced by increased sucrose, invertase activity, reducing sugar, gibberellin, and kinetin hormones. Therefore, leaf defoliation technique can be used to optimize root-cutting chili production in lowland areas through improving physiological activity in root and shoot. GRAPHICAL ABSTRACT